1992
DOI: 10.1200/jco.1992.10.10.1609
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma lipid measurements following cisplatin chemotherapy in patients with germ cell tumors.

Abstract: We have not demonstrated an elevation in total plasma cholesterol after cisplatin chemotherapy as has been reported by previous investigators. Our results suggest that in these patients, cisplatin-containing combination chemotherapy is not associated with a significant adverse effect on plasma lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
1
10
3
Order By: Relevance
“…An elevated serum cholesterol level is regarded as a major risk factor for coronary artery disease, but the biological signifi cance of the reported findings remains to be defined. Recently, Ellis et al [30] published a study which was contradictory to the aforementioned reports [9, 28,29]. Ellis et al [30] did not find significant differences with regard to fasting plasma lipid concentrations between patients treated with chemotherapy for testicular cancer and patients with germ cell tumors who did not receive chemotherapy.…”
Section: Myocardial Infarction and Coronary Artery Diseasecontrasting
confidence: 46%
“…An elevated serum cholesterol level is regarded as a major risk factor for coronary artery disease, but the biological signifi cance of the reported findings remains to be defined. Recently, Ellis et al [30] published a study which was contradictory to the aforementioned reports [9, 28,29]. Ellis et al [30] did not find significant differences with regard to fasting plasma lipid concentrations between patients treated with chemotherapy for testicular cancer and patients with germ cell tumors who did not receive chemotherapy.…”
Section: Myocardial Infarction and Coronary Artery Diseasecontrasting
confidence: 46%
“…Gietema et al [5] and Raghavan et al [27] have described hypercholesterolemia in testicular cancer pa tients who had been treated by cisplatin-based chemo therapy, whereas this has not been confirmed in another report [28], The etiology of this hypercholesterolemia remains unknown. Both overweight and hypogonadism have been discussed [5,27], In our series chemotherapy was not associated with hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 83%
“…After such cytostatic treatment, patients more often had increased serum levels of cholesterol, weight gain, hypertension and decreased renal function (Hansen et al, 1988;Ellis et al, 1992;Raghavan et al, 1992;Bokemeyer et al, 1996;Nord et al, 2003a) than the age-matched general population, or compared to MGCT patients treated by surgery only. Our data support the view of increase of diseases of the circulatory system in patients with MGCT, as our complete cohort of MGCT patients indeed displayed a marginally increased risk of dying from circulatory diseases (SMR: 1.2 (95% CI: 1.0 -1.5)).…”
Section: Discussionmentioning
confidence: 99%
“…These solid cancers develop mostly 10 years or more after radiotherapy, when patients are no longer followed up intensively by their primarily responsible oncological unit. Epidemiologically less established are observations on late adverse events related to obesity, hypercholesterolaemia and decreased kidney function and to cardiovascular events (Hansen et al, 1988;Ellis et al, 1992;Raghavan et al, 1992;Bokemeyer et al, 1996;Fosså et al, 1989;Meinardi et al, 2000;Huddart et al, 2003;Fosså et al, 2003;Nord et al, 2003a). Single-centre reports have indicated that such conditions may be associated with the modern treatment of MGCT, in particular with the use of cisplatin-based chemotherapy.…”
mentioning
confidence: 99%